ENVIRONMENTAL ASPECTS CONTAMINATION AREAS AROUND BURSHTYN TPP - Левченко, В. А.; Вакалюк, І. П.; Карабанович, М. М.; Свистун, І. І.; Овчар, А. І.; Хмурковський, Є. Г. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The main objective of the study was to evaluate the radiation situation of natural and technogenic zone around Burshtyn TPP. Studied exposure dose, specific activity of natural radionuclides in the soil around the TPP ash dump and relatively clean area. The study used dosimeters “Pripyat” – RKS-20.03 “Terra” – MKS-05 IR20, gamma spectrometric complex SBS-30 established that exposure dose in the main area of study in most cases was within the permissible norm – (0,16±0,01) μSv/h, although significantly higher than the results obtained in relatively clean control area – (0,074±0,004) μSv/h. However, the exposure dose at two ash dump was significantly higher, in accordance, (1,18±0,024) μSv/h (0,48±0,043) μSv/h. Along with this in the soil around thermal power was noted an increase in specific activity of radionuclides from families 238U, 232Th and 40K, especially in the areas of ash dumps. In the control area specific activity was much lower and only by 232Th and 40K. Therefore, assessment of background radiation, the distribution of natural radionuclides in soil naturally-technological zone around the power plants represents scientific and practical interest to monitor the possible risk of developing various pathological conditions of the local population.